Pengaruh Penambahan Bayam Merah (Amaranthus tricolor L.) Pada Pembuatan Pempek Ikan Tenggiri Ditinjau Dari Sifat Fisik, Sifat Organoleptik Dan Kadar Zat Besi (Fe) - Sherly Asri Widyaningrum; Setyowati Setyowati; Silvia Dewi (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2019)
Pempek is a typical delicacy from Palembang, which is already accepted as a favorite dish by many people from different strata in Indonesia. Pempek contains animal protein, which is beneficial because it is made of spanish mackerel fish. The pempek which has been added with red spinach is expected to offer an alternative for highly nutritious food, which at the same time serves as the good source of iron (Fe) intake.To determine the influence of adding red spinach of pempek spanish mackerel fish, as viewed from physical properties, organoleptic characteristics, and iron levels (Fe).This research used a pure experimental research with four treatments of red spinach addition (0%, 10%, 20%, and 30%). Physical features were observed subjectively and were analyzed using a descriptive method. Organoleptic characteristics were observed using a hedonic scale test, and were analyzed using Kruskall Wallis H test. Fe contents were observed using a spectrophotometry method, and were analyzed using an Anova test and continued with an LSD test.In terms of taste and aroma features, pempeks with 20% and 30% red spinach addition resemble those of spinach. In terms of color, pempeks with 10%, 20%, and 30% red spinach addition are red. In terms of texture, pempeks with 30% red spinach addition are hard. From organoleptic, color, aroma, taste and texture characteristics test, panelists expressed that they prefered pempeks with 10% red spinach addition. Highest Fe content was found in 30% red spinach addition formula.There is an influence of adding red spinach (amaranthus tricolor L.) to pempek spanish mackerel fish as viewed from physical properties and organoleptic characteristics and iron (Fe) levels.